2019
DOI: 10.1175/mwr-d-18-0194.1
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of the Rotor-Equivalent Wind Speed into the Weather Research and Forecasting Model’s Wind Farm Parameterization

Abstract: Wind power installations have been increasing in recent years. Because wind turbines can influence local wind speeds, temperatures, and surface fluxes, weather forecasting models should consider their effects. Wind farm parameterizations do currently exist for numerical weather prediction models. They generally consider two turbine impacts: elevated drag in the region of the wind turbine rotor disk and increased turbulent kinetic energy production. The wind farm parameterization available in the Weather Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…2). In Siedersleben et al (2018a, b), we obtained best results using a horizontal grid size of 1.67 km.…”
Section: Numerical Setupmentioning
confidence: 90%
See 1 more Smart Citation
“…2). In Siedersleben et al (2018a, b), we obtained best results using a horizontal grid size of 1.67 km.…”
Section: Numerical Setupmentioning
confidence: 90%
“…We use two different sets of vertical levels. The default configuration corresponds to that of Siedersleben et al (2018a, b) with a vertical spacing of 35 m in the lowest 200 m and increasing to 100 m at 1000 m above mean sea level (a.m.s.l. ), corresponding to one vertical level below the rotor area and three within the rotor area for the wind turbine type installed at the MSO and ONO wind farms (case study I; Fig.…”
Section: Numerical Setupmentioning
confidence: 99%
“…We simulate each 24-hour day of August 24 through 27 individually, beginning spin-up at 1200 UTC on the previous day with analysis retained after 0000 UTC. We define the wake effect by comparing a simulation without the WFP to a simulation with the WFP, as in Fitch et al (2012); Lee and Lundquist (2017a); Redfern et al (2019). We use the power and thrust curve of the 1.5-MW PSU generic turbine (Schmitz, 2012) to parameterize the wind turbines, based on the General Electric SLE turbine (80-m hub height and 77-m rotor diameter).…”
Section: Modelingmentioning
confidence: 99%
“…Equation 1is formulated for a Cartesian coordinate system with the indexes i, j, k corresponding to the directions x, y, z, that in turn is equal to the geographic directions West-East, South-North, and the vertical axis with k=0 the level closest to the ground. The variable N ij describes the number of wind turbines within a grid cell i, j; V ij is the horizontal wind speed at hub height at grid cell ij (Redfern et al (2019) showed that during strong shear events rotor-equivalent wind speed result in a different change in 5 TKE). A ikj is the rotor area between the two vertical levels k and k + 1, at a height z k and z k+1 , and V H the horizontal wind speed at hub height.…”
Section: Sandbankmentioning
confidence: 99%